2022
DOI: 10.2147/opth.s390815
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Fellow Eye-Controlled Study of Postoperative Pain and Inflammation Control with an Intracanalicular Dexamethasone 0.4 mg Ophthalmic Insert Following Small Incision Lenticule Extraction

Abstract: Purpose To compare postoperative anterior chamber inflammation, pain, and patient preference following small incision lenticule extraction (SMILE) in eyes treated with a dexamethasone 0.4 mg intracanalicular insert (DEX) or topical prednisolone acetate (PRED). Patients and Methods In this prospective, randomized, fellow eye-controlled trial, 20 patients underwent same-day, bilateral SMILE. One randomly-selected eye of each patient received DEX placed immediately postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…31 A study with SMILE procedures found a similar preference. 32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 Our study indicated that there was no significant difference in conjunctival hyperemia scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A study with SMILE procedures found a similar preference. 32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 Our study indicated that there was no significant difference in conjunctival hyperemia scores.…”
Section: Discussionmentioning
confidence: 99%
“… 31 A study with SMILE procedures found a similar preference. 32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 …”
Section: Discussionmentioning
confidence: 99%